Societas herpetologica italica. Atti del V congresso nazionale, Calci (Pisa), 29 settembre-3 ottobre 2004 - Zuffi, Marco Alberto Luca (Proceedings e report, 2006)
This book contains the proceedings of the Congress, thus making available the extensive range of research performed and in progress. The contributions, in synthetic form, illustrate the methods and results, with the support of data, tables and bibliographies, of 35 studies carried out by research teams of biologists from the universities of Roma-Sapienza, Roma Tor Vergata, Florence, Naples, Turin, Milan, Palermo, Genoa, Pisa, Padua, Pavia, Perugia and Calabria, as well as various museums, study centres, reserves and nature parks.